Sepelvaltimotaudin vaaratekijöiden hoidon vaikutus seerumin lipideihin, erityisesti HDL-kolesteroliin = Effects of long-term multifactorial treatment of coronary heart disease on serum lipids, especially on HDL-cholesterol - Vanhanen, Hannu ([H. Vanhanen], 1986)
English summary.